Universal Values in Islamic Law and Its Relation to Community Religiosity - Muchlis Bahar (Budapest International Research and Critics University, 2022)
The purpose of this study is to analyze universal values in Islamic law and their relationship to the religiosity of society. This research uses qualitative research with a phenomenological analysis approach. The type of data used in this research is secondary data. This research develops the research flow from various points of view, first, by researching universal values and high legal awareness. Next is to examine the effectiveness of the regulations contained in the legislation. The third is to explore the universal values that exist in the teachings of Islam, and the last is to look for the causality of all these things with the level of religiosity of the Indonesian people. Based on the analysis results, it can be concluded that all Islamic teachings contain and are relevant to universal values. Islamic law regulates all aspects of life, both aspects of worship (human relations with God) and aspects of mu'amalah (relationships between humans and their environment, but this is still not implemented by the Indonesian community, although it affects the level of community religiosity.